2006
DOI: 10.1111/j.1467-8624.2006.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Information Processing and Coping Strategies of Shy/Withdrawn and Aggressive Children: Does Friendship Matter?

Abstract: The primary objectives of this investigation were to examine the attributions, emotional reactions, and coping strategies of shy/withdrawn and aggressive girls and boys and to examine whether such social cognitions differ within the relationship context of friendship. Drawn from a sample of 5 th and 6 th graders (M age = 10.79 years; SD = .77), 78 shy/withdrawn, 76 aggressive, and 85 control children were presented with hypothetical social situations that first involved unfamiliar peers, then a mutual good fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
213
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(234 citation statements)
references
References 53 publications
14
213
0
7
Order By: Relevance
“…Three basic functions-Companionship, intimacy-trust, and affection-were found to be crucial criteria distinguishing friends from non-friends among older children during preadolescence and adolescence (e.g., Buhrmester 1990;Parker and Gottman 1989). The formation and maintenance of a satisfactory friendship is an interpersonal achievement built upon a foundation of interpersonal skills (e.g., the child ability's to form affective bonding) and social cognitive skills (e.g., perspective takingTheory of mind) (e.g., Burgess et al 2006;Newcomb and Bagwell 1996;Parker et al 1995;Rose and Asher 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Three basic functions-Companionship, intimacy-trust, and affection-were found to be crucial criteria distinguishing friends from non-friends among older children during preadolescence and adolescence (e.g., Buhrmester 1990;Parker and Gottman 1989). The formation and maintenance of a satisfactory friendship is an interpersonal achievement built upon a foundation of interpersonal skills (e.g., the child ability's to form affective bonding) and social cognitive skills (e.g., perspective takingTheory of mind) (e.g., Burgess et al 2006;Newcomb and Bagwell 1996;Parker et al 1995;Rose and Asher 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These agents of socialization serve as a model for behavior in instruction and illustration of social values, facilitate the internalization of values and the drawing of moral conclusions, and influence the interpretation given by the children to the different behaviors (Eisenberg 1995;Eisenberg & Fabes, 1998). Hence, the educational frameworks have an important role -to mediate between factors of risk such as sociodemographic situation (Runions & Keating, 2007) or factors of resilience such as prosocial behavior and friendships in childhood (Burgess, Wojslawowicz, Rubin, Rose-Krasnor, & Booth-LaForce, 2006;Nelson & Crick, 1999) and social adjustment. Contemporary research studies show that mediation for social behavior through processes of social information processing begins already at the age of the kindergarten (Ziv, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Additional research studies conducted in the field found that distorted patterns of social information processing can be expressed not only in aggressive behavior but also in regressive behavior and social isolation (Dodge et al, 1990). Burgess, Wojslawowicz, Rubin, Rose-Krasnor, and LaForce (2006) proposed that regressive children are characterized by different thinking patterns regarding interpersonal interaction, which were influenced by social experiences of social rejection and victimization. A research study that examined the influence of friendships on the process of social information processing of regressive/shy children found that in contrast to aggressive children these children tended to attribute less external blame and hostile intentions to a familiar peer than to an unfamiliar peer and even tended less to attribute internal blame in cases in which familiar peers were involved (Burgess et al, 2006).…”
Section: The Connection Between Social Information Processing and Socmentioning
confidence: 99%
See 1 more Smart Citation
“…Stresle başa çıkma ile sosyal kaygı arasındaki ilişkilerin incelendiği araştırmalarda (Findlay, Coplan ve Bowker, 2009;Burgess, Wojslawowicz, Rubin, Krasnor ve LaForce, 2006;Baltacı ve Hamarta, 2013) sosyal kaygılı bireylerin daha çok duygu odaklı stresle başa çıkma (kaçınma gibi) stratejilerini kullanması yani uygun olmayan (maladaptive)stratejiler kullanması araştırma bulguları ile benzerlik göstermektedir. Stresle etkili olarak başa çıkabilen üniversite öğrencilerinin probleme yönelik yöntemlerden kendine güvenli ve iyimser yaklaşımları daha fazla kullandıkları, başa çıkamayanların ise duyguya yönelik yöntemlerden boyun eğici ve çaresiz yaklaşımları daha fazla kullanmaktadırlar (Razı, Kuzu, Yıldız ve Arifoğlu, 2009).…”
Section: Tartışma Sonuç Ve öNerilerunclassified